Perceived External CSR from Employees’ Perspective in Nepalese Banking Industry - Shrestha, Renuka; Timalsena, Chiranjibi (Nepal Journal of Multidisciplinary Research, 2023)
In order to better understand how external corporate social responsibility (CSR) efforts in the Nepalese banking industry affect different employee-related outcomes, this paper examines how employees perceive these activities. In this study, staff of Nepalese commercial banks were given questionnaires as part of a descriptive research design in order to gather primary data. The sample size is 120 individuals from an actual sample. This finding suggests that workers have a strong understanding of external CSR activities taking place outside of the organization. It is also clear that employees are conscious of the effects of the CSR efforts and give them a favorable evaluation. The study also investigates the link between work happiness, organizational engagement, and overall views of CSR and employee perceptions of external CSR actions outside the firm. This finding suggests that workers in Nepal's banking industry may see external CSR efforts as positively affecting their loyalty to the firm and job happiness. The relevance of this poll emphasizes how crucial an external CSR strategy is to successfully raising employee happiness and fostering organizational engagement. The report's suggestions for commercial banks are meant to help them match their CSR initiatives with employee expectations and values to foster a productive workplace. Future study objectives include looking at ways to increase employee involvement in CSR initiatives, assessing the long-term effects of CSR efforts, and doing industry comparison studies. Overall, this study helps understand how Nepalese banking industry employees feel about external CSR initiatives.